"Death Diamond" Tracing on Thromboelastography as a Marker of Poor Survival After Trauma. Issue 7 (July 2022) - Farrell, Michael S.; Moore, Ernest E.; Thomas, Anthony V.; Coleman, Julia R.; Thomas, Scott; Vande Lune, Stefani; Marconi, Thomas; Cohen, Mitchell J.; Chapman, Michael P.; Moore, Hunter B.; Walsh, Mark M.; Sixta, Sherry
Background: Improvements in health care innovations have resulted in an enhanced ability to extend patient viability. As a consequence, resources are being increasingly utilized at an unsustainable level. As we implement novel treatments, identifying futility should be a focus. The "death diamond" (DD) is a unique thrombelastography (TEG) tracing that is indicative of failure of the coagulation system, with a mortality rate exceeding 90%. The purpose of this study was to determine if the DD was a consistent marker of poor survival in a multicenter study population. We hypothesize that the DD, while an infrequent occurrence, predicts poor survival and can be used to stratify patients in whom resuscitation efforts are futile. Methods: A retrospective multi-institutional study of trauma patients presenting with TEG DDs between 8/2008 and 12/2018 at four American College of Surgeons trauma centers was completed. Demographics, injury mechanisms, TEG results, management, and survival were examined. Results: A total of 50 trauma patients presented with DD tracings, with a 94% (n = 47) mortality rate. Twenty-six (52%) patients received a repeat TEG with 10 patients re-demonstrating the DD tracing. There was 100% mortality in patients with serial DD tracings. The median use of total blood products was 18 units (interquartile range 6, 34.25) per patient. Discussion: The DD is highly predictive of trauma-associated mortality. This multicenter study highlights that serial DDs may represent a possible biomarker of futility.